Effective gene delivery to Trypanosoma cruzi epimastigotes through nucleofection (2017)
New opportunities have raised to study the gene function approaches of Trypanosoma cruzi after its genome sequencing in 2005. Functional genomic approaches in Trypanosoma cruzi are challenging due to the reduced tools available for genetic manipulation, as well as to the reduced efficiency of the transient transfection conducted through conventional methods. The Amaxa nucleofector device was systematically tested in the present study in order to improve the electroporation conditions in the epimastigote forms of T. cruzi. The transfection efficiency was quantified using the green fluorescent protein (GFP) as reporter gene followed by cell survival assessment. The herein used nucleofection parameters have increased the survival rates (N90%) and the transfection efficiency by approximately 35%. The small amount of epimastigotes and DNA required for the nucleofection can turn the method adopted here into an attractive tool for high throughput screening (HTS) applications, and for gene editing in parasites where genetic manipulation tools remain relatively scarce.